1997
DOI: 10.1136/gut.41.4.452
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori independent chronological change in gastric acid secretion in the Japanese

Abstract: Background-Gastric acid secretion in Japanese subjects decreases with aging. One of the possible causative mechanisms of this attenuated acid secretion is speculated to be a Helicobacter pylori induced chronic gastritis. The infection rate of this microorganism has decreased recently in Japan. Aims-To investigate whether gastric acid secretion has altered over the past 20 years, and if so, what the influence of H pylori infection might be in the Japanese population. Subjects and methods-Gastric acid secretion,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
144
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(147 citation statements)
references
References 30 publications
3
144
0
Order By: Relevance
“…Gastric acid secretion in Japanese individuals has been demonstrated to be increasing due to a decrease in the rate of H. pylori infection and the Westernization of eating habits, especially a high protein intake (29). In this study, we investigated changes in the degree of gastric mucosal atrophy and found that it decreased over the 10-year period in both men and women.…”
Section: Discussionmentioning
confidence: 95%
“…Gastric acid secretion in Japanese individuals has been demonstrated to be increasing due to a decrease in the rate of H. pylori infection and the Westernization of eating habits, especially a high protein intake (29). In this study, we investigated changes in the degree of gastric mucosal atrophy and found that it decreased over the 10-year period in both men and women.…”
Section: Discussionmentioning
confidence: 95%
“…Secondly, the population has become increasingly overweight [27] , and obesity may lead to an increase in intragastric pressure [15] . Thirdly, it has been reported Japanese patients have a high incidence of H pylori infection and this leads to an atrophic pattern of gastritis with low acid secretion [28,29] . The declining prevalence of H pylori infection [30] , due to improved hygiene conditions and widespread use of eradication therapy in Japan could also have paradoxically contributed to the increased frequency of GERD.…”
Section: Figurementioning
confidence: 99%
“…It was reported that gastric acid secretion has increased over the past 20 years in Japanese subjects, however, gastric acid secretion is still lower in Japanese subjects than in Europeans or Americans, which may be one reason for lower esophageal acid exposure and smaller number of acidic reflux events in the present study. 21 In this study, weakly acidic reflux was defined as a decrease of more than 1 pH unit with the nadir pH remaining above 4, while non-acidic reflux was defined as no change of pH or a decrease of less than 1 pH unit. Because Sifrim et al 22 reported the importance of weakly acidic reflux (using the same definition as ours) in patients with suspected GERD, we defineded weakly acidic refluxes separately from non-acidic refluxes.…”
Section: Discussionmentioning
confidence: 99%